Characterization of the multimeric structure of poly(A)-binding protein on a poly(A) tail - Ryoichi Sawazaki (Nature Portfolio, 2018)
Abstract Eukaryotic mature mRNAs possess a poly adenylate tail (poly(A)), to which multiple molecules of poly(A)-binding protein C1 (PABPC1) bind. PABPC1 regulates translation and mRNA metabolism by binding to regulatory proteins. To understand functional mechanism of the regulatory proteins, it is necessary to reveal how multiple molecules of PABPC1 exist on poly(A). Here, we characterize the structure of the multiple molecules of PABPC1 on poly(A), by using transmission electron microscopy (TEM), chemical cross-linking, and NMR spectroscopy. The TEM images and chemical cross-linking results indicate that multiple PABPC1 molecules form a wormlike structure in the PABPC1-poly(A) complex, in which the PABPC1 molecules are linearly arrayed. NMR and cross-linking analyses indicate that PABPC1 forms a multimer by binding to the neighbouring PABPC1 molecules via interactions between the RNA recognition motif (RRM) 2 in one molecule and the middle portion of the linker region of another molecule. A PABPC1 mutant lacking the interaction site in the linker, which possesses an impaired ability to form the multimer, reduced the in vitro translation activity, suggesting the importance of PABPC1 multimer formation in the translation process. We therefore propose a model of the PABPC1 multimer that provides clues to comprehensively understand the regulation mechanism of mRNA translation.